Exploring the characteristics of SnO₂ nanoparticles doped organic blend for low-cost nanoelectronics applications - Algidsawi, A.J.K.; Hashim, A.; Hadi, A.; Habeeb, M.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
The PVA/PVP/SnO₂ nanostructure films were fabricated using the casting technique. The structure, dielectric, and optical characteristics of PVA/PVP/SnO₂ nanostructures were studied for pressure sensors. Results of studying the dielectric characteristics showed that the dielectric constant, dielectric losses, and electrical conductivity of the blend are enhanced with the rise of SnO₂ nanoparticles (NPs) content. The dielectric constant and dielectric losses are reduced, while the conductivity rises with the increase in frequency. The dielectric constant increases from 2.53 to 7.41, and dielectric losses rise from 0.5 to 2, while the conductivity increases from 2.82·10⁻¹¹ S/cm up to 1.11·10⁻¹⁰ S/cm. The results of measuring the optical characteristics have indicated that the absorbance rises with increasing SnO₂ NPs content. The energy gap of the blend has been reduced from 4.9 to 4.65 eV with the rise in SnO₂ NPs content. The optical constants have been improved with the rise in SnO₂ NPs content. Results of studying the pressure sensors have shown that their capacitance grows with the pressure increase. Плівкові наноструктури PVA/PVP/SnO₂ виготовляли методом лиття. Досліджено структуру, діелектричні та оптичні характеристики наноструктур PVA/PVP/SnO₂ для датчиків тиску. Результати дослідження діелектричних характеристик показали, що діелектрична проникність, діелектричні втрати та електропровідність суміші підвищуються зі збільшенням вмісту наночастинок SnO₂. Діелектрична проникність і діелектричні втрати зменшуються, у той час як провідність зростає зі збільшенням частоти. Діелектрична проникність збільшується з 2,53 до 7,41, а діелектричні втрати зростають з 0,5 до 2, тоді як провідність зростає з 2,82·10⁻¹¹ до 1,11·10⁻¹⁰ С/см. Результати дослідження оптичних характеристик показали, що поглинання зростає зі збільшенням вмісту наночастинок SnO₂. Ширина забороненої зони суміші зменшується з 4,9 до 4,65 еВ зі збільшенням вмісту наночастинок SnO₂. Оптичні константи покращуються зі збільшенням вмісту наночастинок SnO₂. Результати досліджень датчика тиску показали, що ємність зростає зі збільшенням тиску.